The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11071881
|View full text |Cite
|
Sign up to set email alerts
|

Waste Heat and Water Recovery System Optimization for Flue Gas in Thermal Power Plants

Abstract: Fossil-fueled power plants present a problem of significant water consumption, carbon dioxide emissions, and environmental pollution. Several techniques have been developed to utilize flue gas, which can help solve these problems. Among these, the ones focusing on energy extraction beyond the dew point of the moisture present within the flue gas are quite attractive. In this study, a novel waste heat and water recovery system (WHWRS) composed of an organic Rankine cycle (ORC) and cooling cycles using singular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Boiling number (𝐵𝐵 𝑜𝑜 ) is a dimensionless number which gives the ratio of actual heat flux (𝑞𝑞 𝐻𝐻 " ) to the maximum attainable heat flux (𝐺𝐺 × 𝑙𝑙 𝑅𝑅134𝑎𝑎 ) from complete evaporation of liquid. In Equation (20), 𝐺𝐺 and 𝑙𝑙 𝑅𝑅134𝑎𝑎 are the mass velocity and latent heat of R134a respectively flowing inside the tube respectively.…”
Section: B Flow-boiling Of R134a Inside Tubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Boiling number (𝐵𝐵 𝑜𝑜 ) is a dimensionless number which gives the ratio of actual heat flux (𝑞𝑞 𝐻𝐻 " ) to the maximum attainable heat flux (𝐺𝐺 × 𝑙𝑙 𝑅𝑅134𝑎𝑎 ) from complete evaporation of liquid. In Equation (20), 𝐺𝐺 and 𝑙𝑙 𝑅𝑅134𝑎𝑎 are the mass velocity and latent heat of R134a respectively flowing inside the tube respectively.…”
Section: B Flow-boiling Of R134a Inside Tubesmentioning
confidence: 99%
“…al [19] presented an experimental study on lab-scale ORC, and concluded that this ORC system could produce additional power from flue gas at 160 o C with thermal efficiency of 3.3%, and aftercooler could recover 50% of water in the flue gas by cooling it below HTFF 131-3 30-40 o C. In 2019, Shamsi et. al [20] studied a novel waste heat and water recovery system (WHWRS) integrated with ORC and cooling cycles using a singular working fluid undergoing a phase change. From this study, it was found that for a 600 MW power plant the water capture efficiency was 50%.…”
Section: Introductionmentioning
confidence: 99%
“…This study will focus on adapting waste heat recovery (WHR) methods that have been proven to work in applications such as fossil fuel plants [7][8][9] to a low temperature hydrogen fuel cell. WHR is used to recover heat that would otherwise be wasted, boosting the plants overall efficiency by using a secondary, bottoming thermodynamic cycle to generate extra power.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], several thermodynamic cycles were presented for the study of the recovery of waste heat from the exhaust gases of internal combustion engines; it was concluded that, the Rankine cycle has the best performance for heat recovery from exhaust gases. Syed et al [8] showed that ORC cycles are well suited to heat recovery for low and medium temperatures as they offer significant advantages over conventional steam cycles [9] in [8]. Other studies compare an ORC without a recuperator and an ORC with a recuperator [10,11].…”
Section: Introductionmentioning
confidence: 99%